Who Put Hate in My Sunday Paper? (American Journal of Islam and Society, 2009)
Uncovering the Israeli-Republican-Evangelical Networksbehind the “Obsession” DVDSomething strange showed up inside the Sunday newspapers of millions ofAmericans last September. Thematerial included alongside comics, coupons,and advertisement for local stores is a controversial DVD called “Obsession:Radical Islam’sWar against theWest.” Some 28 million copies of it were distributedfor free in this fashion. In some ways, this campaign’s scale and ideologicalvenom were unprecedented: many newspapers stated that they hadnever previously distributed freeDVDs as inserts, certainly nothing with sucha charged content. The copies were distributed not randomly across the country,but only in the “swing states” (viz., Florida, Pennsylvania, Ohio, Michigan,Wisconsin, Iowa, Colorado, etc.) that were seen as toss-ups in theNovember presidential elections between McCain and Obama. Obviously,someone was trying to influence theAmerican electorate by playing on fearmongeringand hate-mongering themes. But who?Who was behind thismassive,multi-million dollar campaign?Answering that question proved harder than one might think, as thegroups behind this DVD have worked hard to hide their tracks. The connections,which were partially concealed in the DVD and the distribution campaign,took one from groups in Israel to pro-Israel lobby organizations in the ...